Pain Intensity as Prognostic Factor in Cancer Pain Management. Issue 1 (11th November 2014) - Mercadante, Sebastiano; Porzio, Giampiero; Adile, Claudio; Aielli, Federica; Cortegiani, Andrea; Caruselli, Amanda; Casuccio, Alessandra
Abstract Aim The aim of this study was to prospectively assess the prognostic value of initial pain intensity and its duration in advanced cancer patients. Methods A prospective study was conducted in a sample of patients with cancer requiring pain control. Patients underwent standard analgesic strategies used in our palliative care units. Pain intensity was measured at admission (T0) and after successful dose titration or opioid/route switching within a week (Ts). Patients were also asked about their pain intensity reported 15 days before admission (T‐15). Doses of opioids and duration of opioid use were recorded. Patients were also assessed for the presence of incident pain, neuropathic pain, alcoholism, delirium, and symptom intensity, including items representing psychological distress. One week after or at time of stabilization (Ts), the opioid response was clinically graded as follows: (1) good pain control; (2) adequate pain control requiring more aggressive opioid escalation; (3) adequate pain control associated with the occurrence of adverse effects; (4) incapacity to achieve pain control within a week. Opioid escalation indexes and days for dose finding were also recorded. Results Pain intensity at T0 and at T‐15, opioid doses, duration of opioid therapy, and age were associated with more complex analgesic therapies, which were effective in almost all patients within a week. Conclusion High levels of pain intensity, often due to previous undertreatment, are predictive of more complex analgesic treatment. Opioid tolerance, as well as younger age, may also play a role.